2023
DOI: 10.1111/pcn.13548
|View full text |Cite
|
Sign up to set email alerts
|

Moderation effect of the eveningness chronotype on the relationship between ADHD tendency and Internet addiction

Abstract: CYP1A2 enzymes, lowering the expected plasma levels of certain antipsychotics. 8 Therefore, asenapine add-on treatment might improve schizophrenia symptoms in individuals who had smoked in the previous 6 months. The RTS subgroup that included individuals with initial PANSS-P ≥ 20 (n = 17) had a more significant reduction in PANSS-P at the endpoint than the subgroup that included individuals with initial PANSS-P < 20 (Table S3). Other associations between some clinical factors and PANSS scores (Table S3) might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…While the distinctions between NT1, NT2, and IH remain pivotal, the intricate relationship between EDS and psychiatric disorders, particularly attention deficit hyperactivity disorder (ADHD), adds another layer of complexity (9). Recent studies have shown a strong coexistence between EDS and ADHD (10)(11)(12). For example, 61% of the patients with central hypersomnia with EDS exhibit ADHD-like symptoms (13), whereas 38% of individuals with ADHD have EDS (10).…”
Section: Introductionmentioning
confidence: 99%
“…While the distinctions between NT1, NT2, and IH remain pivotal, the intricate relationship between EDS and psychiatric disorders, particularly attention deficit hyperactivity disorder (ADHD), adds another layer of complexity (9). Recent studies have shown a strong coexistence between EDS and ADHD (10)(11)(12). For example, 61% of the patients with central hypersomnia with EDS exhibit ADHD-like symptoms (13), whereas 38% of individuals with ADHD have EDS (10).…”
Section: Introductionmentioning
confidence: 99%